Safety and outcomes of pre-operative portal vein embolization using N-butyl cyanoacrylate (Glue) in hepatobiliary malignancies: A single center retrospective analysis - Mukund, Amar; Mondal, Aniket; Patidar, Yashwant; Kumar, Senthil (Indian Journal of Radiology and Imaging, 2019)
Aims and Objectives: To evaluate the outcome of preoperative portal vein embolization (PVE) using N-butyl cyanoacrylate (NBCA) for change in future liver remnant (FLR) volume, biochemical changes, and procedure-related complications. The factors affecting FLR hypertrophy and the rate of resection was also evaluated for this cohort. Materials and Methods: From 2012 to 2017, PVE utilizing NBCA mixed with lipiodol (1:4) was performed using percutaneous approach in 28 patients with hepatobiliary malignancies with low FLR. All patients underwent volumetric computed tomography (CT) assessment before and at 3–5 weeks after PVE and total liver volume (TLV), FLR volume, and FLR/TLV ratio, changes in portal vein diameter and factors affecting FLR were evaluated. Complications and the resectability rate were recorded and analyzed. Result: PVE was successful in all 28 patients. The mean FLR increased by 52% ± 32% after PVE (P < 0.0001). The FLR/TLV ratio was increased by 14.2% ± 2.8% (P < 0.001). Two major complications were encountered without any impact on surgery. There was no significant change seen in liver function test and complete blood counts after PVE. Eighteen patients (64.28%) underwent hepatic resection without any liver failure, and only three patients developed major complication after surgery. Remaining ten patients did not undergo surgery because of extrahepatic metastasis detected either on follow-up imaging or staging laparotomy. Patients with diabetes showed a lower rate of hypertrophy (P < 0.05). Conclusion: Preoperative PVE with NBCA is safe and effective for increasing FLR volume in patients of all age group and even in patients with an underlying liver parenchymal disease with hepatobiliary malignancy. Lesser hypertrophy was noted in patients with diabetes. A reasonable resectability was achieved despite having a high rejection in gall bladder cancer subgroup due to rapid disease progression.
Keywords: Future liver remnant; N-butyl cyanoacrylate glue; Portal vein embolization